Neutron Imaging of Cadmium Sorption and Transport in Porous Rocks - Cordonnier, Benoît; Pluymakers, Anne; Tengattini, Alessandro; Marti, Sina; Kaestner, Anders; Fusseis, Florian; Renard, François (Frontiers in Earth Science, 2019)
Understanding fluid flow in rocks is crucial to quantify many natural processes such as ground water flow and naturally triggered seismicity, as well as engineering questions such as displacement of contaminants, the eligibility of subsurface waste storage, geothermal energy usage, oil and gas recovery and artificially induced seismicity. Two key parameters that control the variability of fluid flow and the movement of dissolved chemical species are i) the local hydraulic conductivity, and ii) the local sorption properties of the dissolved chemical species by the solid matrix. These parameters can be constrained through tomography imaging of rock samples subjected to fluid injection under constrained flow rate and pressure. The neutron imaging technique is ideal to explore fluid localization in porous materials due to the high but variable sensitivity of neutrons to the different hydrogen isotopes. However, until recently, this technique was underused in geology because of its large acquisition time. With the improved acquisition times of newly set-up neutron beamlines, it has become easier to study fluid flow. In the current set of experiments, we demonstrate the feasibility of in-situ 2D and 3D time-lapse neutron imaging of fluid and pollutant percolation in rocks, in particular that of cadmium salt. Cadmium is a hazardous compound that is found in many electronic devices, including batteries and is a common contaminant in soil and groundwater. It also exhibits higher contrast in neutron attenuation with respect to heavy water, and is therefore an ideal tracer. Time-lapse 2D radiographies and 3D neutron tomographies of the samples were acquired on two neutron beamlines (ILL, France and SINQ, Switzerland). We performed two sets of experiments, imbibition and injection experiments, where we imaged in-situ flow properties, such as local permeability and interactions between cadmium and the solid rock matrix. Our results indicate that even within these cm-scale porous rocks, cadmium transport follows preferential pathways, and locally interacts within the limestone samples. Our results demonstrate that the use of neutron imaging provides additional insights on subsurface transport of pollutants.